Spatial Variation of the Suicide Phenomenon in Urban Centers of Basra Governorate - Hachim Lazim, Assist . Prof. Dr. Ibrahim (Basra studies journal, 2025)
This research aims to shed light on the phenomenon of suicide in the urban centers of Basra Governorate and the factors contributing to its increase in recent years. A descriptive and analytical approach was adopted, utilizing criminal statistics data from the Basra Governorate Police Directorate to identify the primary causes and motives behind the notable rise in suicide cases. The study focuses on suicide in the urban centers of Basra Governorate during the period 2018–2022, providing a clear picture of its spatial distribution and the reasons and factors contributing to its prevalence. The findings reveal that mental disorders accounted for the highest proportion of suicides, representing 72.2% of all cases in urban centers. Conversely, physical illnesses and alcohol and drug abuse were the least significant causes, accounting for only 1.9%. The research concludes with key findings and recommendations aimed at mitigating and addressing this phenomenon.